PENGARUH TOTAL QUALITY MANAGEMENT (TQM) TERHADAP KINERJA MANAJERIAL DENGAN SISTEM PENGHARGAAN SEBAGAI VARIABEL PEMODErRASI (STUDI PADA SUPERMARKET DI MATARAM) - Sri Ayu Febrianti; I Gusti Putu Bagus Suastina; Muhammad Bahrul Ulum; Eka Putrianti (Sekolah Tinggi Pariwisata Mataram, 2021)
The aim of this study is to analyzed the effect of Total Quality Management (TQM) on managerial performance and the reward system as the moderating variable that may affect the relationship of Total Quality Management (TQM) on managerial performance. The type of this research is associative. Respondents consisting of managers and staff with the lowest level of supervisor in the entire supermarket in Mataram, as many as 66 respondents. Sampling technique is census. Using simple regression analysis and Moderated Regression Analysis (MRA) as analysis. The results showed that TQM significantly influence the performance of managerial and the reward system doesn’t influence the relationship of TQM on managerial performance